C-Kit, a Double-Edged Sword in Liver Regeneration and Diseases - Wang, Weina; Shui, Liyan; Liu, Yanning; Zheng, Min (Frontiers in Genetics, 2021)
Previous studies have reported an important role of c-kit in embryogenesis and adulthood. Activation of the SCF/c-kit signal transduction pathway is customarily linked to cell proliferation, migration and survival thus influence hematopoiesis, pigmentation, and spermatogenesis. The role of c-kit in the liver is controversial, it is however argued that it is a double-edged sword in liver regeneration and diseases. First, liver c-kit+ cells, including oval cells, bile epithelial cells, and part of hepatocytes, participate in liver tissue repair by regenerating target cells according to the type of liver injury. At the same time, c-kit+ mast cells, act as immature progenitors in circulation, playing a critical role in liver fibrosis. Furthermore, c-kit is also a proto-oncogene. Notably, c-kit overexpression regulates gastrointestinal stromal tumors. Various studies have explored on c-kit and hepatocellular carcinoma, nevertheless, the intricate roles of c-kit in the liver is largely understudied. Herein, we extensively summarize previous studies geared towards providing hints for future clinical and basic research.